BIOMECHANICAL STUDY TO ASSESS THE VARIATIONS BETWEEN MALE AND FEMALE IN LONG JUMP - Abdel-Rahman Akl (Sport Scientific And Practical Aspects, 2025)
The purpose of this study is assessment the variations between male and female in long jump and determine the causes that led to the differences between male and female in long jump for improve the performance. Ten long jump players are high level athletes participated in this study (Five male and five female). They were the elite athletes in Egypt. The long jumps were performed on a two-dimensional analysis, marker position data were obtained by a high-speed camera (JVC GR – DVL 9800) at a frequency of 240 Hz, video point v 2.5 2D motion analysis for Biomechanical parameters, and statistically T-test for independent samples and Change Ratio were used to compare results for male and female. The results of biomechanical parameters between male and female ranged between (0.89% - 34.57%) in favor of male or female, male surpassed in velocity of free leg swing during takeoff phase, Selected a biomechanical parameters group influential in the long jump performance (pre- last stride resultant velocity, last stride resultant velocity, horizontal velocity at touch down, resultant velocity at touch down, resultant velocity of the free leg at touch down, horizontal velocity at takeoff, resultant velocity at takeoff, resultant velocity of the free leg at takeoff, total takeoff time, linear momentum at touch down, kinetic energy at touch down, linear momentum at takeoff, and kinetic energy at takeoff), and confirmed by the strong correlation between these parameters and long jump distance.